Investigation of Hyalomma turanicum and Hyalomma asiaticum in Pakistan, with notes on the detection of tickborne Rickettsiales - Ullah, Zafar; Liaqat, Iram; Khan, Mehran; Alouffi, Abdulaziz; Almutairi, Mashal M.; Apanaskevich, Dmitry A.; Tanaka, Tetsuya; Ali, Abid (Frontiers in Veterinary Science, 2024)
There is limited information on the occurrence of Hyalomma turanicum and Hyalomma asiaticum ticks, as well as associated Rickettsia, Anaplasma, and Ehrlichia species in Pakistan. Addressing this knowledge gap, the current study aimed at morphomolecular confirmation of these ticks and molecular assessment of associated Rickettsiales bacteria (Rickettsia, Anaplasma, and Ehrlichia spp.) in Balochistan, Pakistan. A total of 314 ticks were collected from 74 of 117 (63.2%) hosts, including 41 of 74 (55.4%) goats and 33 of 74 (44.5%) sheep. Subsequently, a subset of microscopically identified ticks was subjected to DNA extraction and PCR to amplify 16S rDNA and cox1 fragments. Additionally, gltA, ompA, and ompB fragments were targeted for Rickettsia spp. and 16S rDNA fragments for both Anaplasma and Ehrlichia spp. The 16S rDNA and cox1 sequences of Hy. turanicum demonstrated 100% identity with those of the same species previously reported from Pakistan. The 16S rDNA and cox1 sequences of Hy. asiaticum exhibited 99.52 and 100% identities, respectively, with corresponding species reported from China, Kazakhstan, and Turkey. The gltA, ompA, and ompB fragments associated with Hy. turanicum showed 100% identities with Rickettsia aeschlimannii reported from Egypt, Italy, Kazakhstan, Kenya, Pakistan, and Senegal. The 16S rDNA sequences of Anaplasma sp. and Ehrlichia sp. associated with both Hy. asiaticum and Hy. turanicum exhibited 99.67 and 100% identities with unknown Anaplasma sp. and Ehrlichia sp. reported from Morocco and Pakistan, respectively. In the 16S rDNA and cox1 phylogenetic trees of ticks, Hy. turanicum and Hy. asiaticum from the current study clustered with their respective species. Similarly, in gltA, ompA, and ompB phylogenetic trees of Rickettsia, R. aeschlimannii of the present study clustered with the same species, whereas Anaplasma sp. and Ehrlichia sp. of this study clustered with undetermined Anaplasma spp. and Ehrlichia spp. in the 16S rDNA phylogenetic tree of Anaplasmataceae. Among the DNA samples from the screened ticks, a coinfection rate of R. aeschlimannii, Anaplasma sp., and Ehrlichia sp. (2 of 80, 2.5%) was observed in Hy. turanicum, whereas individual infection rates were noted as follows: R. aeschlimannii (8 of 80, 10%), Anaplasma sp. (5 of 80, 6.3%), and Ehrlichia sp. (5 of 80, 6.3%). This study marks the first record of molecular characterization of Hy. turanicum and Hy. asiaticum as well as the detection of associated R. aeschlimannii, Anaplasma sp., and Ehrlichia sp. in Balochistan, Pakistan.